Diagnostics and treatment of traumatic brain injury in children - D. V. Kolmakov (Бюллетень сибирской медицины)
In this work, we have analyzed 2 774 case records of children after traumatic brain injury for the period of 2003 to 2007 (based on materials of the Tomsk Municipal Children’s Hospital No. 4). The age structure and causes of a traumatic brain injury have been analyzed. Most often complaints of children coming to the hospital are revealed, as well as typical changes in the cerebral hemodynamics (from the data of по данным rheoencephalography) and some parameters characterizing the neurological status of patients immediately after the injury and six months later. Based on the analysis of case records and health status questionnaires of children having traumatic brain injury up to six months later, it is shown that parents of patients in some cases do not adhere doctor’s recommendations after leaving the hospital. The therapy of traumatic brain injury in children requires successive treatment in hospital and at home and development of simple and acceptable rehabilitation schemes for children.